Analyzing (Condition Based Maintenance) Level 1 On Substation Equipment PT. PLN Persero Berastagi - Ramadan Sembiring; Solly Aryza; Hamdani (Sean Institute, 2021)
Condition Based Maintenance (CBM) is a proposed maintenance program based on a decision to collect data from factory condition measurements. CBM is an attempt to save money by carrying out essential inspections only when something odd happens in production. Data acquisition (information gathering) refers to the process of capturing and storing data or information that is useful for CBM purposes during the data acquisition (information gathering) stage. This is the most basic step in implementing a CBM program to identify and predict equipment failures. This study aims to see Condition Based Maintenance (CBM) level 1 on substation equipment. CBM applications are used to streamline the storage and monitoring of inspection data equipment by observing machine/work equipment parameters, such as vibration measurement, oil level, temperature, pressure, flow and ultrasonic flow detectors. The research approach used in this study consisted of three steps, namely literature review, testing, and observation by processing data using the mean life Calculator (LM). There are two types of treatment and condition data collected in the CBM program. Based on the results of monitoring with CBM at the PT PLN Persero Berastagi substation, incident data consists of information about what happened (damage, installation, inspection, etc.) and what has been done (repair, prevention, oil change, etc.). ) in less than a month.